Well , are you familiar with the factor theorem ?

If not , note that for a polynomial P(x),(x-a) is a factor of P(x) if and only if P(a)=0 .

Notice that the constant term for the equation above is -6 .

Hence if (x-a) were to be a factor of P(x) , then a must be a factor of -6.

a=+/-1,+/-2,+/-3,+/-6

Substitute :

If x=1 , P(1)=1+2-5-6=-8 , hence (x-1) is NOT a factor .

If x=-1,P(-1)=-1+2+5-6=0 , hence (x+1) IS a factor .

Try doing this for all values of a stated above and you should get all the factors for this equation .